High-Strength Albumin Hydrogels With Hybrid Cross-Linking - Lu, Shaoping; Zhu, Lin; Wang, Qilin; Liu, Zhao; Tang, Chen; Sun, Huan; Yang, Jia; Qin, Gang; Sun, Gengzhi; Chen, Qiang (Frontiers in Chemistry, 2020)
Natural protein-based hydrogels possess excellent biocompatibility; however, most of them are weak or brittle. In the present work, high strength hybrid dual-crosslinking BSA gels (BSA DC gels), which have both chemical cross-linking and physical cross-linking, were fabricated by a facile photoreaction-heating process. BSA DC gels showed high transparency (light transmittance of 90%) and high strength. At optimal conditions, BSA DC gel exhibited high compressive strength (σc,f) of 37.81 ± 2.61 MPa and tensile strength (σt,f) of 0.62 ± 0.078 MPa, showing it to be much stronger than physically cross-linked BSA gel (BSA PC gel) and chemically cross-linked BSA gel (BSA CC gel). More importantly, BSA DC gel displayed non-swelling properties while maintaining high strength in DI water, pH = 3.0, and pH = 10.0. Moreover, BSA DC gel also demonstrated large hysteresis, rapid self-recovery, and excellent fatigue resistance properties. It is believed that our BSA DC gel can potentially be applied in biomedical fields.